Spiritual capital in the development of the Avestan values: Human problems (Zien Journal of Social Sciences and Humanities, 2022)
The present article analyzes the ethical norms and principles of Zoroastrian philosophy in the context of the human problem. Besides, the author believes that the codes of morality and spiritual baggage have been formed over many centuries. In the process of expanding of socio-historical practice, insights, and the development of human consciousness, there is a gradual bringing together and systematization of moral precepts. The moral ideas recorded in the “Avesta” are a kind of conglomerate of the most ancient moral concepts of primitive society, which subsequently changed, enriched and developed in accordance with socio-historical conditions. However, at the same time, in terms of content, they form the basis of the modern concept of spiritual and moral human capital.